Thailand’s National and Health Development Status in the World and Asia - Suchatsoonthorn, Chaiyaporn; Sealim, Sumaporn (Journal of Health Science of Thailand, 2019)
The objective of this study was to assess Thailand’s national and health development level and status compared with other Asian countries and in the world. Aiming to be one among the top-three in health development of Asia in 2032-2036, the study explored the level and status of Thailand against the 20-year National Strategic Plan for Public Health (2017-2036) based on secondary data from 5 global updated reports in 2018 of 5 sources for the world ranking, rating and trends in the national and health development index. The results showed that Thailand was at the moderate level in the national and health development status, for instance, rank and score in SPI (70th, 67.35) for SPI-Health and wellness (46th, 70.02), SDGI (59th, 69.2) except SDG3-good health and well-being (76.7) lower than 20 Asian countries, HDI (83th, 0.755) and quite good in GCI (38th, 67.5) including GCI-Human capital: Health (42th, 87.3), HI (46th, 6.072). Thailand’s scores in all these indexes were greater than the mean and median of Asia. However, Thailand could meet the targets for health development only in GCI and SPI. For the ranks and scores in 3 health and 5 country development index, there were 8 countries (Singapore, South Korea, Japan, Qatar, Cyprus, Israel, Kuwait, Labanon) and 3 countries (Malaysia, Singapore, Israel) better than Thailand respectively. For results of development, Thai population had healthy life expectancy at birth 74.9 years. Some health problems including maternal and child care, universal health coverage and access to essential health services had been improved whereas some health problems were still the challenges such as non-communicable diseases, air pollution, HIV in adults, stunting children. The severe health problems which were still main challenges included traffic injuries, tuberculosis, suicide, homicide, adolescent pregnancy, low exclusive breast feeding, shortage of medical personnel and beds in hospital, and low health expenditure.